2015
DOI: 10.1186/s12886-015-0094-z
|View full text |Cite
|
Sign up to set email alerts
|

Case series and techniques of Descemet’s Stripping Automated Endothelial Keratoplasty for severe bullous keratopathy after birth injury

Abstract: BackgroundTo evaluate clinical outcomes of Descemet’s Stripping Automated Endothelial Keratoplasty (DSAEK) for severe bullous keratopathy that develop as a late complication of endothelial injury to the baby during forceps delivery at birth.Case presentationsFour eyes (four patients; mean age, 51.5 years) with severe bullous keratopathy as a late complication of forceps delivery at birth were enrolled. All patients had amblyopia from childhood due to cloudy cornea. Nontheless, DSAEK was indicated in these pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…4,9 Corneal edema occurs at a late stage in the adulthood of these patients and probably plays no role in the development and degree of amblyopia; moreover, in some cases forceps lesions may spare the central optical zone but cause more paracentral or peripheral stromal edema (Fig. 1).…”
Section: Discussionmentioning
confidence: 97%
“…4,9 Corneal edema occurs at a late stage in the adulthood of these patients and probably plays no role in the development and degree of amblyopia; moreover, in some cases forceps lesions may spare the central optical zone but cause more paracentral or peripheral stromal edema (Fig. 1).…”
Section: Discussionmentioning
confidence: 97%
“…Most of the authors have reported a normal IOP in children with FIDMTs. Various authors such as Ponchel,[ 14 ] Kobayashi,[ 20 ] Kancherla,[ 21 ] and Hayashi[ 22 ] reported raised IOP after surgical interventions such as Descemet’s puncture with air injection, Descemet stripping automated endothelial keratoplasty (DSAEK), and penetrating keratoplasty (PKP). The presumed mechanism could be localized iridocorneal adhesions, pupillary block glaucoma, inflammation, or steroid use.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…These associated injuries can indirectly aid clinicians in diagnosing missed FIDMTs. Few of the injuries, as reported by McDonald[ 6 ], Kobayashi,[ 20 ] and Simpson,[ 23 ] include…”
Section: Clinical Featuresmentioning
confidence: 99%
See 2 more Smart Citations